Cultivating proficient and efficacious L2 English speakers via VoiceThread-mediated self- and peer assessments - Min-Hsun Liao (Humanities & Social Sciences Communications)
Abstract Despite growing interest in technology-mediated language assessment, limited research has examined the differential effects of online self- versus peer assessment on L2 speaking development. This mixed-methods study investigated how VoiceThread-mediated self-assessment (SA) and peer assessment (PA) influenced the English speaking proficiency and self-efficacy of adult EFL learners. Drawing on sociocultural theory and self-regulated learning frameworks, this research explored the impact of different online assessment approaches on language learning outcomes. Thirty-seven English majors at a Taiwanese university were randomly assigned to SA (n = 19) and PA (n = 18) conditions. Over one academic year, SA participants provided narrative self-evaluations of their recorded speeches on VoiceThread, while PA participants evaluated peers’ recordings and narrated their comments. Data were collected through (a) pre-post oral proficiency evaluations using adapted TOEFL speaking rubrics (interrater reliability = 0.89), (b) the English-speaking Self-efficacy Questionnaire (α = 0.92), and (c) post-intervention interviews and surveys. ANCOVA results revealed that the SA group demonstrated significantly greater gains in overall oral proficiency (F(1, 34) = 15.603, p < 0.001, η 2 = 0.32) and self-efficacy (F(1, 34) = 5.07, p < 0.05, η 2 = 0.13). The SA group showed significantly higher performance in accuracy and linguistic complexity compared to the PA group, although no significant between-group differences emerged in fluency or pronunciation (p > 0.05). Regarding self-efficacy, the SA group demonstrated significantly greater improvement in overall speaking confidence, particularly in interlocutory self-efficacy. Qualitative analyses indicated that SA participants developed stronger metacognitive awareness and self-regulatory strategies, although both groups reported technological and affective challenges. These findings suggest that SA may be particularly effective for developing productive language skills and speaking confidence in technology-mediated environments. The study extends current understanding of assessment modality effects on L2 development and offers practical implications for implementing online speaking assessment in EFL contexts.